Exploratory review of ecological indicators in oil palm cultivation - Amir, Mohd Murshid; Harun, Nor Zalina; Zakariya, Khalilah (2014)
Over the past 50 years, oil palm has become an important major crop in the agricultural sector in Southeast Asia. Its expansion is widely distributed in countries such as Malaysia, Indonesia, Thailand and Vietnam. This phenomenon is response to the large increase in the world demand for vegetable oils and biofuel needs, which is expected to double by 2020. Oil palm industry can be seen as one of the key factors to contribute in establishing the economic that largely benefits major holders like estates companies and smallholders in rural areas. However, aside from the positive impacts of socioeconomic growth, rapid expansion of the oil palm industry has brought negative impacts to the environment particularly in the air, water, land, soil, habitat, biodiversity and landscape pattern. Through monocultures practices within the plantation, a lot of chemical fertilizers and pesticides are used, which contribute to a dramatic change of the environment that affect climate and human health. The effects of oil palm have been broadly discussed in Asia particularly pertaining social and environmental issues. Methods to assess the sustainability of oil palm cultivation to promote balance in the ecosystem that might loss during the conversion is still vague. Previous studies have researched on measuring the sustainability of oil palm cultivation through the development of indicators. However, there are still gaps in identifying the dimensions and levels of the relevant indicators. The indicators should be developed by referring to the present socioeconomic and ecological situation. Development of ecological indicators is important component in the sustainability of oil palm cultivation. This paper reviews the basic concepts of the current development of ecological indicators in oil palm cultivation through identifying relevant indicators and challenges for development and implementing the indicators.